Isolation and Characterization of Multipotent Canine Urine-Derived Stem Cells - Yan Xu; Tao Zhang; Yang Chen; Qiang Shi; Muzhi Li; Tian Qin; Jianzhong Hu; Hongbin Lu; Jun Liu; Can Chen (Stem Cells International)
Current cell-based therapies on musculoskeletal tissue regeneration were mostly determined in rodent models. However, a direct translation of those promising cell-based therapies to humans exists a significant hurdle. For solving this problem, canine has been developed as a new large animal model to bridge the gap from rodents to humans. In this study, we reported the isolation and characterization of urine-derived stem cells (USCs) from mature healthy beagle dogs. The isolated cells showed fibroblast-like morphology and had good clonogenicity and proliferation. Meanwhile, these cells positively expressed multiple markers of MSCs (CD29, CD44, CD90, and CD73), but negatively expressed for hematopoietic antigens (CD11b, CD34, and CD45). Additionally, after induction culturing, the isolated cells can be differentiated into osteogenic, adipogenic, chondrogenic, and tenogenic lineages. The successful isolation and verification of USCs from canine were useful for studying cell-based therapies and developing new treatments for musculoskeletal injuries using the preclinical canine model.